Inspiring the New Workforce: Transformational Leadership and Job Satisfaction as Drivers of Organizational Citizenship Behavior in Generation Z Civil Servants - Diah Sofiah; Sholihah, Husna (Journal of Educational, Health and Community Psychology, 2025)
In 2023, Generation Z ASN (State Civil Apparatus) workers accounted for 6% of the workforce, totaling 268,920 employees. Previous research suggests that Generation Z holds different work values compared to earlier generations. These differences may lead Generation Z workers to be less inclined toward Organizational Citizenship Behavior (OCB), despite OCB being a crucial factor in organizational performance. This study aims to examine the OCB of Generation Z ASN workers and its relationship with Transformational Leadership, with Job Satisfaction as a mediating factor. The research involved 365 Generation Z ASN employees working in the Government of Province X, selected through purposive sampling. Data was collected using the OCB Scale, Transformational Leadership Scale, and Job Satisfaction Scale. The analysis was conducted using Partial Least Square – Structural Equation Modeling (PLS-SEM). The findings indicate that both Transformational Leadership and Job Satisfaction have a positive and significant impact on the OCB of Generation Z ASN employees. All proposed hypotheses were supported. These results highlight the critical role of Transformational Leadership and Job Satisfaction in enhancing OCB among Generation Z ASN workers.